Technology Transfers and the Clean Development Mechanism in a North-South General Equilibrium Model - Linda Sahlén; Thomas Aronsson; Kenneth Backlund (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper analyzes the potential welfare gains of introducing a technology transfer from Annex I to non-Annex I in order to mitigate greenhouse gas emissions. Our analysis is based on a numerical general equilibrium model for a world economy comprising two regions, North (Annex I) and South (non-Annex I). As our model allows for labor mobility between the formal and informal sectors in the South, we are also able to capture additional aspects of how the transfer influences the Southern economy. In a cooperative equilibrium, a technology transfer from the North to the South is clearly desirable from the perspective of a global social planner, since the welfare gain for the South outweighs the welfare loss for the North. However, if the regions do not cooperate, then the incentives to introduce the technology transfer appear to be relatively weak from the perspective of the North; at least if we allow for Southern abatement in the pre-transfer Nash equilibrium. Finally, by adding the emission reductions associated with the Kyoto agreement to an otherwise uncontrolled market economy, the technology transfer leads to higher welfare in both regions.
Keywords: D58; D62; Q52; 330; Climate Policy; Technology Transfer; Kyoto Protocol; General Equilibrium; Clean Development Mechanism